Cyberlearning Model with Microlearning Strategies to Enhance Edutechpreneurship Skills for University Students - H., Nurhikmah; Mappalotteng, Abdul Muis; Hakim, Abdul; Dewi, Laksmi; Hidayanti, Abna; Dewi, Utari (PT Mattawang Mediatama Solution, 2025)
The rapid growth of the education technology (edutech) sector demands the development of entrepreneurial skills among university students to foster innovation and address educational challenges. This study employed the 4D instructional design model—Define, Design, Develop, and Disseminate—by creating an online platform that features personalized learning paths, interactive modules, collaborative tools, and real-time analytics. This research design was employed with 100 university students specializing in education and technology. Over eight weeks, participants engaged with microlearning modules focused on key entrepreneurial concepts and collaborated on projects simulating real-world Edutech scenarios. The findings show that online microlearning models prioritize technological accessibility, quality content, engagement, and flexibility, which are in high demand. Microlearning with short modules and interactive videos improves comprehension and engagement. Task and Concept Analyses frame learning and deepen understanding of key concepts, enabling students to apply learning outcomes. The cyberlearning model used criterion-referenced exams, evaluation tools, and interactive media like short movies, infographics, and gamification to increase edutechpreneurship. A Wilcoxon Signed Rank Test analysis revealed a significant difference between pre-test and post-test scores (p-value < 0.05). The cyber learning model boosted students' Edutechpreneurship skills. Edutechpreneurship, which combines educational technology and entrepreneurship, improves online learning and promotes entrepreneurship. This model requires entrepreneurship education in online learning platforms. This research offers valuable insights into innovative educational practices that prepare students to lead and innovate in the evolving EdTech industry. The model is effective and relevant to augment depth, readability, and personalization for an optimal learning experience